Challenges and instructor strategies for transitioning to online learning during and after the COVID-19 pandemic: a review of literature - Richards, Keith; Thompson, Brittany Myles Wright (Frontiers in Communication, 2023)
The COVID-19 pandemic triggered an unprecedented shift to online learning, significantly impacting the higher education landscape. This paper examines the challenges faced by faculty and students during the rapid transition to online instruction and explores best practices for delivering effective online courses. The increased adoption of online learning created stress for faculty and resulted in academic setbacks for students. Although challenges are present strategies exist to help faculty create rich online learning environments. One important element is engagement, which looks at both student engagement with the material and with their classmates and faculty. In addition to working on student engagement the faculty were now in a position that required a new type of expertise to manage online interactions, which can be much different from their experiences in traditional classrooms. Insufficient time for proper course adaptation and limited knowledge of online teaching methods added to these challenges. Effective online delivery requires careful planning, utilization of advanced instructional technologies, and creating an immersive and interactive learning environment. Faculty must also adapt their teaching strategies to accommodate the unique challenges of online instruction. This review highlights the significance of a quality learning management system (LMS) as the backbone of online courses. An effective LMS facilitates course management, content delivery, and student interaction. Future considerations include providing comprehensive faculty support and training, promoting effective communication and collaboration among students, and incorporating interactive elements into online lessons. The following will provide lessons learned from the COVID-19 pandemic which will help faculty to improve their instructional competence and social presence in the online classroom.